2007
DOI: 10.1016/j.euje.2007.07.002
|View full text |Cite
|
Sign up to set email alerts
|

The influence of myocardial scar and dyssynchrony on reverse remodeling in cardiac resynchronization therapy

Abstract: In this study LV dyssynchrony remains the most important determinant of response to CRT, even in the presence of posterolateral scar provided atrioventricular and interventricular pacing intervals are optimized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 23 publications
1
21
0
2
Order By: Relevance
“…Moreover, only a few studies indicated having used optimization of AV delay, VV interval, or both. 27,28,31,32 Interestingly, these latter studies did not find a negative influence of infarction, including a study from the group that reported the negative effect of scar on CRT response in nonoptimized patients. 32 Therefore, our findings are consistent with observation in human studies, showing that pacing outside the infarct in patients with an LV free wall infarct still carries a benefit.…”
Section: Comparison With the Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, only a few studies indicated having used optimization of AV delay, VV interval, or both. 27,28,31,32 Interestingly, these latter studies did not find a negative influence of infarction, including a study from the group that reported the negative effect of scar on CRT response in nonoptimized patients. 32 Therefore, our findings are consistent with observation in human studies, showing that pacing outside the infarct in patients with an LV free wall infarct still carries a benefit.…”
Section: Comparison With the Literaturementioning
confidence: 99%
“…6,[27][28][29][30] At least part of the explanation for a poor response in patients with ICM may be that pacing (usually LV posterolateral) within the scar hampers CRT response, 7,9 but this finding is not confirmed by other studies. 31,32 In many studies, the position of the scar, of the pacing lead, and the combination of the two is not exactly known. Moreover, only a few studies indicated having used optimization of AV delay, VV interval, or both.…”
Section: Comparison With the Literaturementioning
confidence: 99%
“…Prior studies have demonstrated a relationship between the extent of global LV scar burden measured by 18 F-FDG PET, SPECT, or MRI and the response to CRT (7,(9)(10)(11)(12)(13)(14)(15)(16). In addition to confirming an association between response and scar burden, our exploitation of the additional CT modality revealed positioning of the LV pacemaker in nonviable myocardial areas for 4 of 7 nonresponders.…”
Section: Discussion Scar Burden and LV Lead Positionmentioning
confidence: 99%
“…Reverse remodelling was observed in only four patients with posterolateral (PL) scarring, nine patients without PL scarring and 25 patients with no scarring. However, in a multivariate analysis, only the presence of dyssynchrony could predict an acute response to CRT (62). In a head-to-head comparison of TDI with magnetic resonance imaging (MRI) assessing septal to lateral delays, a good correlation was observed between the two modalities (63).…”
Section: D Echomentioning
confidence: 99%